A Comparative Analysis of Female and Male Language Features in The Movie “The Idea of You” - Widiantari, Ni Pande Putu Erna; Juniartha, I Wayan (Language Circle: Journal of Language and Literature, 2025)
This study focuses on gender language patterns within sociolinguistic, analyzing the women and men language features used by the two main characters in “The Idea of You” movie by Robinne Lee. The aim is to identify and describe the women and men language features reflected in the dialogues from two main characters. A descriptive qualitative method was conducted to analyze the data, which was sourced from the interactions between the two characters. The observation method was utilized to collect the data, and two theories were applied: Lakoff (1975) to identify women language features whereas to identify the men language features proposed from Coates’s theory (2004). The findings revealed nine out of ten features were present by the two main characters, with the exception of precise color terms. All five features of men language features were also identified. Mostly, intensifier is the most frequently used women language features, reflecting how the main characters communicate more expressively. In contrast, command and directives were the dominant men language features that employed by the two main characters, revealing their tendency to assert control and direct actions in their interactions.